A kinetic study on the nitrification process in the upflow submerged biofilter reactor. Issue 27 (6th December 2022) - Polat Bulut, Ayben; Aslan, Şükrü
ABSTRACT: In extent of this study, ammonium removal from wastewater through biological nitrification process was performed in upflow biofilm reactors. The effects of hydraulic retention time (HRT) and nitrogen loading rate (NLR) on the nitrification process were investigated. For the nitrification process, the optimum HRT and NLR were determined to be 80 hr and 0.044 kg/m 3 .day, respectively. It is observed that the efficiency increased from 53% to 96% along with the increase in HRT from 22 hr to 80 hr and the decrease in NLR from 0.165 kg/m 3 .day to 0.044 kg/m 3 .day.The substrate consumption kinetics were studied in the attached growth reactor, and the Monod kinetic model, first-order kinetic model, modified Stover-Kincannon and Grau second-order kinetic models were examined. For the substrate consumption kinetic study, experimental studies were performed at 125, 150, 175, 200, 225 mg NH4 -N/L substrate concentrations and 62 hr at HRT during the nitrification process. As a result of the considering kinetic studies, it was determined that the kinetic study was suitable for the modified Stover-Kincannon kinetic model that had the highest coefficient of regression by 0.997 and when the effluent NH4 -N concentrations and NH4 -N removal efficiencies calculated using kinetic models were examined, it was observed that the results closest to the experimental results (4.5, 10.1, 19.7, 26.2 and 42.3 mg NH4 -N/L) were obtained through the modified Stover-Kincannon model (4.16, 10.71, 18.92, 28.12 and 39.51 mg NH4 -N/L). GRAPHICAL ABSTRACT: UF0001